Climate change and its potential impact on the conservation of the Hoary Fox, Lycalopex vetulus (Mammalia: Canidae) - Gutiérrez, Eliécer E.; Heming, Neander M.; Penido, Gabriel; Dalponte, Julio C.; Lacerda, Ana Cristyna Reis; Moratelli, Ricardo; Bubadué, Jamile de Moura; da Silva, Leonardo Henrique [UNESP]; Wolf, Mariana M.; Marinho-Filho, Jader (Springer Nature, 2019)
We aimed to assess the potential impact of climate change on the geographic distribution of areas holding suitable climatic conditions for the presence of Lycalopex vetulus, and to discuss the implications of such distribution for the conservation of the species. We employed correlative modeling analyses to infer the geographic distribution of climatically suitable conditions for the species on climatic scenarios for the present and for years 2050 (average for 2041–2060) and 2070 (average for 2061–2080). The data consisted of species occurrences and 5 bioclimatic variables containing interpolated and averaged information on seasonal variation of temperature and precipitation. Models were projected onto climatic scenarios employing three different global circulation models and two representative concentration pathways. For each of these scenarios, we quantified the expected changes in area (km2) holding suitable climatic conditions and how much of that area is expected to be within the current Brazilian system of protected areas. Our results reveal that climate change represents a major threat for the survival of L. vetulus by drastically reducing its habitat availability in a period of time no longer than five decades from now. Experimental physiological and behavioral studies are necessary to assess whether L. vetulus is able to adequately tolerate under climatic conditions different to those under which the species is currently present.
Keywords: Brazil; Carnivora; Cerrado; Climatic suitability; Distribution